Comprasion of primary school maths program a case study for Cosova-Turkey - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
Education, individual behavior is to change the direction of the requested. The behaviour to be gained through education should be suitable to the individual and social demands. Moreover, education is the basis of increasing the development, increasing employment and raising the national competion power. Stage for the Cosova government institutions, education, especially primary education as the first step is very important. To this end, training programs of other countries are examined to create the best appropriate training programs for Cosova is attempting. One of these studies is realized in this paper which including comparative study between the primary 6th grade math program Turkey and Cosova. The results obtained have been interpreted mutually. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Education; comparative education; education program; maths program